Policing protest: the post-democratic state and the figure of black insurrection - Passavant, Paul A. (Global and insurgent legalities, 2021)
Introduction: Policing protest and the post-democratic state -- Aesthetic government : neoliberal authoritarianism and the post-democratic right of expression -- New York's mega-event security legacy and the postlegitimation state -- Policing the uprising : Occupy Wall Street and order maintenance policing -- Violent appearances and neoliberalism's disintegrated political subjects -- Political antagonism : #BlackLivesMatter and the postlegitimation, postdemocratic state -- Conclusion: Policing protest and neoliberal authoritarianism.